Fenomena Ketertarikan Orang Tua Pada Rumpun Pendidikan Agama Islam di Madrasah Tsanawiyah Miftahul Khoir Kabupaten Tasikmalaya - Muhamad Nur (AL-Ikhtiar : Jurnal Studi Islam, 2026)
This study aims to analyze the phenomenon of parental interest in the Islamic Religious Education (PAI) cluster at Miftahul Khoir Middle School in Tasikmalaya Regency and identify the factors influencing these preferences in choosing an education for their children. The study used a qualitative approach with a phenomenological approach to explore the experiences, perceptions, and meanings parents attach to PAI cluster learning. The research informants consisted of parents of students, the madrasah principal, PAI cluster teachers, and students selected purposively. Data were collected through observation, in-depth interviews, and documentation. Then, they were analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The validity of the data was tested through triangulation of sources and techniques. The results indicate that parental interest in PAI clusters is driven by the belief that religious education is the primary foundation for the formation of students' faith, morals, worship, and character. Furthermore, increasing moral challenges resulting from the development of digital technology, social media, and changes in the social environment encourage parents to prioritize religious education. Other factors that strengthen this interest include teacher competence, the madrasah's religious culture, religious habituation programs, and good communication between the madrasah and parents. Research findings indicate that parents' decisions in choosing a madrasah are influenced not only by academic quality but also by the institution's ability to shape students' religious character through the integration of learning and school culture. Therefore, strengthening the quality of Islamic Religious Education (PAI) learning, enhancing teacher professionalism, and ongoing collaboration between the madrasah, families, and the community are important strategies for increasing parental trust in Islamic education and supporting the formation of a generation with faith, noble character, and the ability to face the challenges of modern development. These findings also align with various studies showing that parental preference for Islamic schools is influenced by the quality of religious education, the school's religious culture, and family involvement in the educational process. Abstrak Penelitian ini bertujuan untuk menganalisis fenomena ketertarikan orang tua terhadap rumpun Pendidikan Agama Islam (PAI) di Madrasah Tsanawiyah Miftahul Khoir Kabupaten Tasikmalaya, serta mengidentifikasi faktor-faktor yang memengaruhi preferensi tersebut dalam memilih pendidikan bagi anak. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian fenomenologi untuk menggali pengalaman, persepsi, dan makna yang diberikan orang tua terhadap pembelajaran rumpun PAI. Informan penelitian terdiri atas orang tua peserta didik, kepala madrasah, guru rumpun PAI, dan peserta didik yang dipilih secara purposive. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan, dengan keabsahan data diuji melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa ketertarikan orang tua terhadap rumpun PAI didorong oleh keyakinan bahwa pendidikan agama merupakan fondasi utama dalam pembentukan akidah, akhlak, ibadah, dan karakter peserta didik. Selain itu, meningkatnya tantangan moral akibat perkembangan teknologi digital, media sosial, dan perubahan lingkungan sosial mendorong orang tua untuk memberikan prioritas yang lebih besar terhadap pendidikan agama. Faktor lain yang memperkuat ketertarikan tersebut adalah kompetensi guru, budaya religius madrasah, program pembiasaan keagamaan, serta terjalinnya komunikasi yang baik antara madrasah dan orang tua. Temuan penelitian menunjukkan bahwa keputusan orang tua memilih madrasah tidak hanya dipengaruhi oleh kualitas akademik, tetapi juga oleh kemampuan lembaga dalam membentuk karakter religius peserta didik melalui integrasi pembelajaran dan budaya sekolah. Dengan demikian, penguatan mutu pembelajaran rumpun PAI, peningkatan profesionalisme guru, serta kolaborasi yang berkelanjutan antara madrasah, keluarga, dan masyarakat menjadi strategi penting dalam meningkatkan kepercayaan orang tua terhadap pendidikan Islam dan mendukung terbentuknya generasi yang beriman, berakhlakul karimah, serta mampu menghadapi tantangan perkembangan zaman. Temuan ini juga selaras dengan berbagai kajian yang menunjukkan bahwa preferensi orang tua terhadap sekolah Islam dipengaruhi oleh kualitas pendidikan agama, budaya religius sekolah, dan keterlibatan keluarga dalam proses pendidikan.